Framework for autonomy in Southeast Asia's plural societies - Ferrer, Miriam Coronel (2009)
Perhaps drawing inspiration from the success of East Timnor in separating from Indonesia, post-Cold War Southeast Asia faces a resurgence of ethnic strife. Ethnic mobilization, with its threat to the integrity of the nation-states as presently constructed, is thus emering as a key security issue for these states and the region. This study developed a framework for autonomy that can be useful to nation-states confronted with this problem. The elements of the framework were extracted from a survey of contemporary ethnic mobilization in four Southeast Asian countries - namely, in Southern Philippines, Southern Thailand, Aceh in Indonesia and Burma - and corresponding governmental responses. The scheme effectively illustrates how the nation-state territory can be preserved which sovereignty is diffused or devolved through various measures, including spatial arrangements that can maximize the criteria of distinctiveness and efficiency; and assuasive and corrective mechanisms, with their respective upward and downward streams, that respond to and find a balance among conflicting needs and interests.